Landscapes and Social Transformations on the Northwest Coast Colonial Encounters in the Fraser Valley - Oliver, Jeff (University of Arizona Press, 2022)
The Fraser Valley in British Columbia has been viewed historically as a typical setting of Indigenous-white interaction. Jeff Oliver now reexamines the social history of this region from pre-contact to the violent upheavals of nineteenth and early twentieth century colonialism to argue that the dominant discourses of progress and colonialism often mask the real social and physical process of change that occurred here-change that can be more meaningfully tied to transformations in the land. The Fraser Valley has long been a scene of natural resource appropriation-furs and fish, timber and agriculture-with settlement patterns and land claims centering on the use of these materials. Oliver demonstrates how social change and cultural understanding are tied to the way that people use and remake the landscape. Drawing on ethnographic texts, archaeological evidence, cartography, and historical writing, he has created a deep history of the valley that enables us to view how human entanglements with landscape were creative of a variety of contentious issues. By capturing the multiple dynamics that were operating in the past, Oliver shows us not only how landscape transformations were implicated in constructing different perceptions of place but also how such changes influenced peoples' understanding of history and identity. This groundbreaking work examines engagement between people and the environment across a variety of themes, from aboriginal appropriation of nature to colonists' reworking of physical and conceptual geographies, demonstrating the consequences of these interactions as they permeated various social and cultural spheres. It offers a new lens for viewing a region as it provides fresh insight into such topics as landscape change, perceptions of place, and Indigenous-white relations.